Techniques for nano emulsion in milk and its application: A review - Siti Norazilah Maklin; Norliza Julmohammad; Suryani, S.; Sariah Saalah; Jahurul Haque Akanda; Siti Norliyana A.R; Norziana, J. (Penerbit UPM, 2025)
The present review provides a comprehensive overview of nano emulsion preparation techniques and their impact on dairy milk and milk foam properties. It highlights high- energy methods utilizing mechanical forces to produce nanoscale droplets, thus enhancing emulsion stability, and allowing precise control over droplet size. While effective for various production scales, these methods require significant energy and sophisticated equipment, with potential heat generation affecting sensitive compounds. Conversely, low-energy methods rely on thermodynamic changes, offering cost-effective solutions for heat-sensitive compounds, despite facing challenges in scalability and formulation specificity. The incorporation of nanometer-sized droplets into dairy milk significantly influences foaming behavior and texture modulation, improving foam stability and foamability. Smaller fat globule sizes promote long-term physical stability, addressing common issues like foam destabilization and coalescence. Understanding the interactions between milk quality, fat content, and processing conditions reveals opportunities for enhancing dairy product quality. The present review underscores the potential of nano emulsions into optimizing dairy milk properties, ultimately revolutionizing dairy processing, and providing manufacturers with innovative tools to meet consumer demand for superior texture and stability in milk-based products.